STUDY OF MICROFLORA PATHOGENIC TO FISH IN BIOREMEDIATED SEWAGE EFFLUENT - Almas Khurshid; I Ahmad; Rehana Kausar (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2013)
To assess the suitability of bioremediated sewage effluent from Shehzad Town, Islamabad for fish cultivation, it was tested for the presence of microflora pathogenic to fish and also for its water quality, at National Agriculture Research Centre (NARC), Islamabad. There was no significant difference found in the microflora of fresh and bioremediated sewage effluent and no evidence of disease causing species was observed during the study. A total of 15 fungal isolates and 7 bacterial isolates were obtained from bioremediated sewage effluent. Identified isolated microflora was found to be non-pathogenic to fish. Most prominent fungal species were that of Aspergillus, Alternaria, and Penicillium, whereas Pseudomonas, Proteus, and Elizabeth were prominent bacterial species in both fresh and bioremediated sewage effluent.